Pressure effects on the kinetics of reactions in aqueous solution. - Chen, David T. Y. (University of Ottawa (Canada), 1958)
The rates of the alkaline hydrolysis of some esters and amides, and of the alkaline fading of certain organic dyes, have been studied over a range of hydrostatic pressures from atmospheric pressure to 16,000 pounds per square inch. In the case of the ester and amide hydrolyses the results obey van 't Hoff's law, the logarithm of the rate constant varying linearly with the pressure. From the slopes of the lines values of DeltaV*, the volume of activation, were calculated; they fell in the range of -10 to -17 cc, per mole. These negative volumes of activation are to be correlated with the negative entropies of activation for the reactions. It is suggested that the results maybe explained in terms of the hypothesis that the activated complex is much more polar than the reactants. In the case of the alkaline fading of dyes the results were somewhat more complicated, the van 't Hoff law not always being obeyed. In the case of crystal violet the rate was found to be independent of the pressure. With brom phenol blue and phenol phthalein the rates were markedly increased by pressure, so that the volumes of activation are negative. These negative volumes of activation are found to be correlated with the entropies of activation for the reactions. An explanation for the results is given in terms of the changes in polarity during the course of the reactions.
Keywords: Chemistry, General.